2019
DOI: 10.1124/jpet.119.261222
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile of the Novel Antiepileptic Drug Candidate Padsevonil: Characterization in Rodent Seizure and Epilepsy Models

Abstract: The antiepileptic drug (AED) candidate, (4R)-4-(2-chloro-2,2-difluoroethyl)-1-{[2-(methoxymethyl)-6-(trifluoromethyl)imidazo[2,1b][1,3,4]thiadiazol-5-yl]methyl}pyrrolidin-2-one (padsevonil), is the first in a novel class of drugs that bind to synaptic vesicle protein 2 (SV2) proteins and the GABA A receptor benzodiazepine site, allowing for pre-and postsynaptic activity, respectively. In acute seizure models, padsevonil provided potent, dose-dependent protection against seizures induced by administration of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
(61 reference statements)
1
33
0
Order By: Relevance
“…In vivo binding data indicate 50% SV2A and BZD site occupancy at 0.2 and at 36 mg/kg, respectively, supporting in vitro results, with 100-fold lower PSL potency at the BZD site compared with SV2A. In the accompanying report, PSL is shown to be active in a variety of nonclinical seizure and epilepsy models in the 0.1-10 mg/kg dose range (Leclerq et al, 2019). This finding corroborates observations that moderateto-high SV2 occupancy is associated with antiseizure activity and that low-level BZD site occupancy potentiates this effect (Kaminski et al, 2009a).…”
Section: Levetiracetamsupporting
confidence: 52%
See 1 more Smart Citation
“…In vivo binding data indicate 50% SV2A and BZD site occupancy at 0.2 and at 36 mg/kg, respectively, supporting in vitro results, with 100-fold lower PSL potency at the BZD site compared with SV2A. In the accompanying report, PSL is shown to be active in a variety of nonclinical seizure and epilepsy models in the 0.1-10 mg/kg dose range (Leclerq et al, 2019). This finding corroborates observations that moderateto-high SV2 occupancy is associated with antiseizure activity and that low-level BZD site occupancy potentiates this effect (Kaminski et al, 2009a).…”
Section: Levetiracetamsupporting
confidence: 52%
“…The objectives of the studies reported here are to characterize the interactions of PSL with its intended therapeutic targets and to determine its selectivity for these targets using an array of validated in vitro and in vivo techniques. The pharmacological profile of PSL in nonclinical models of seizures and epilepsy is reported in the accompanying article (Leclerq et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…23 With both acute and repeated (twice daily for 4 consecutive days) dosing, Padsevonil increased the threshold for PTZ-induced seizures to the same extent, indicating that tolerance was not developed. 22 In contrast, diazepam, a full agonist at the BZD site, showed a reduced ability to increase the PTZ threshold after repeated dosing. 22 Clinical evidence also supports the observation that partial agonists may be associated with a lower risk of tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…22 In contrast, diazepam, a full agonist at the BZD site, showed a reduced ability to increase the PTZ threshold after repeated dosing. 22 Clinical evidence also supports the observation that partial agonists may be associated with a lower risk of tolerance. Clobazam, a partial agonist at the BZD site, has been used for the treatment of patients with Lennox-Gastaut syndrome for many years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation